Pengaruh Metode Index Card Match dalam Pelajaran Al-Qur’an Hadist terhadap Hasil Belajar Siswa Kelas X Madrasah Aliyah - Maulidina Rahmawati; Sulaiman Sulaiman (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The lack of variety in the learning strategies used and the poor performance of MAS Asy Syarif Koto Laweh class X students in Al-Qur'an Hadith subjects were the driving forces behind this study. 1) To understand the learning process utilizing the tag matching method is the goal of this study. 2) Using the tag matching method, determine the learning results. 3) to assess the impact of the card matching technique. A Hadith lecture on student learning outcomes uses card comparison to